2017
DOI: 10.1002/cam4.1108
|View full text |Cite
|
Sign up to set email alerts
|

Comparative molecular profiling of HPV‐induced squamous cell carcinomas

Abstract: Approximately 5% of all cancer incidences result from human papillomavirus (HPV) infection. HPV infection most commonly leads to cancers of the anogenital region or oropharynx. It is unknown whether different HPV‐mediated cancers collectively share a molecular signature and it is important to determine if there are targetable alterations common to different types of HPV‐positive tumors. We analyzed 743 p53 wild‐type samples of anal, cervical, oropharyngeal, and vulvar squamous cell carcinomas which underwent m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
44
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 58 publications
1
44
0
Order By: Relevance
“…SCCs are the most common histological type as the most common etiological agent responsible for cervical cancer is HPV which most commonly affects the lining cervical [19,23] epithelium. HSIL was the common histological subtype in premalignant lesions in the present study which is in concordance to the studies done by Jeffers et al [24] The mean age of presentation of malignant lesions (49.04 ± 10.42 years) is almost similar to that reported by Rajaram et al [25] (52.1 ± 12.46 years), Tan et al [26] (51.1 years), Koncar et al [27] (50 years), and Tan et al [28] (50.3 years). Furthermore, the mean age of presentation of premalignant lesions (41.00 ± 8.89 years) is younger than that of malignant lesions.…”
Section: Discussionsupporting
confidence: 92%
“…SCCs are the most common histological type as the most common etiological agent responsible for cervical cancer is HPV which most commonly affects the lining cervical [19,23] epithelium. HSIL was the common histological subtype in premalignant lesions in the present study which is in concordance to the studies done by Jeffers et al [24] The mean age of presentation of malignant lesions (49.04 ± 10.42 years) is almost similar to that reported by Rajaram et al [25] (52.1 ± 12.46 years), Tan et al [26] (51.1 years), Koncar et al [27] (50 years), and Tan et al [28] (50.3 years). Furthermore, the mean age of presentation of premalignant lesions (41.00 ± 8.89 years) is younger than that of malignant lesions.…”
Section: Discussionsupporting
confidence: 92%
“…These data are remarkably consistent with those from patients with OPSCC showing an inverse relationship between hrHPV infection and disruptive TP53 mutations in the primary tumor . Furthermore, overexpression of p16 INK4a , as surrogate marker for HPV‐driven carcinomas, was recently found to be associated with TP53 wild‐type status in both primary and metastatic site of OPSCC and other HPV‐associated cancers, that is, cervical, anal, and vulvar SCC . In a series of HNSCC inclusive of 20 NSCCUP, Bersani et al found that the frequency of hotspot mutations in several oncogenes and tumor suppressor genes, including TP53 , was similarly less frequent in HPV‐positive OPSCC and HPV‐positive NSCCUP compared to HPV‐negative OPSCC …”
Section: Discussionmentioning
confidence: 99%
“…24,[26][27][28] Furthermore, overexpression of p16 INK4a , as surrogate marker for HPV-driven carcinomas, was recently found to be associated with TP53 wild-type status in both primary and metastatic site of OPSCC and other HPV-associated cancers, that is, cervical, anal, and vulvar SCC. 29 In a series of HNSCC inclusive of 20 NSCCUP, Bersani et al found that the frequency of hotspot mutations in several oncogenes and tumor suppressor genes, including TP53, was similarly less frequent in HPV-positive OPSCC and HPV-positive NSCCUP compared to HPV-negative OPSCC. 30 In our TP53 mutation analysis, the amplification and sequencing success rate was limited by poor quality and low concentration of DNA isolated from FFPE tissue, which is often observed in retrospective studies using archived F I G U R E 1 Flow diagram of the HPV and TP53 status results from formalin-fixed, paraffin-embedded neck squamous cell carcinoma of unknown primary included in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, PTEN deletion, identi ed in Case 2, frequently accompanied HPV-induced squamous cell carcinoma. 18 These ndings imply that HPV may play a leading role in TC carcinogenesis.…”
Section: Discussionmentioning
confidence: 96%